Cuentas por cobrar de la empresa BAMAREX S.A. del Cantón Baba, en el periodo 2023. - Bonoso Rodríguez, Salma María (2024)
The case study on the accounts receivable of BAMAREX S.A. in Baba for the year 2023 addresses the management of these accounts and their impact on the company's liquidity and profitability. The central issue lies in the need to understand how the management of accounts receivable affects two critical financial aspects. The justification for the study is based on its importance for the stability and growth of the company, as poor management can compromise its operational capacity. The main objective was to analyze the management of accounts receivable and its impact on liquidity and profitability through the review of financial statements. The methodology used combined qualitative and quantitative approaches, including document review and the calculation of financial indicators such as accounts receivable turnover and average collection period. The analysis revealed that the accounts receivable turnover decreased, and the average collection period increased in 2023, indicating lower efficiency in receivables management. The conclusions suggest the need to review and strengthen credit and collection policies to improve the company's operational liquidity and financial stability.